A water-skiing chresmodid from the Middle Jurassic in Daohugou, Inner Mongolia, China (Polyneoptera: Orthopterida) - Zhang, Xin-Wen; Ren, Dong; Pang, Hong; Shih, Chung-Kun (Zootaxa, 2008)
A new genus with a new species (Jurachresmoda gaskelli gen. et sp. nov.) of Chresmodidae (Insecta: Polyneoptera: Orthopterida) is described and illustrated. They were collected from the Middle Jurassic in Daohugou, Jiulongshan Formation, Inner Mongolia (Nei Mongol Autonomous Region), China. J. gaskelli have fringing hairs on tarsi and a part of tibiae of mid legs. These hairs and leg structures were probably associated with its water-skiing locomotion on freshwater. A high number of tarsomeres, e. g. ultra-articulated tarsi as reported in other species of Chresmodidae, are also found for this new species. But, these true tarsi are mixed with some wrinkles resulted from dehydration and compression during fossilization process. Nymphs of the new species are also described. This is the first time that long and segmented cerci of the nymph are described in Chresmodidae.